Social interaction and successful aging in elderly with chronic diseases - Sumarsih, Gusti; Freska, Windy; Desriza, Tasya; Hernowo, Bingar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Social interaction plays a crucial role in supporting successful aging, particularly among elderly individuals with chronic diseases such as hypertension, diabetes mellitus, and heart disease. This study aims to analyze the impact of social interaction on successful aging among elderly people visiting the Andalas Health Center in Padang City. A causal-comparative design with a cross-sectional approach was used, involving 266 elderly individuals who visited the health center between May and June 2023. Data were collected using a Likert-based questionnaire measuring social interaction and successful aging. The results of the correlation test reveal that various aspects of social interaction positively influence dimensions of successful aging, including lifestyle, physical health, and mental health. Participation in social activities had the highest correlation with lifestyle (0.60) and physical health (0.48), while close social relationships correlated positively with lifestyle (0.49), physical health (0.33), and mental health (0.35). Furthermore, satisfaction with social support had the greatest impact on mental health (0.49), followed by physical health (0.39) and lifestyle (0.44), emphasizing the importance of both active social participation and feeling supported in maintaining overall well-being. These findings suggest that enhancing social interaction, particularly through community engagement and strong interpersonal relationships, is a significant factor in improving the quality of life and supporting successful aging, especially for elderly individuals with chronic conditions. Therefore, community-based interventions and health programs that promote social participation and strengthen social support networks are recommended to foster healthier aging.